Impact of integrated nutrient management on growth and yield of rice under different water-saving cultivation systems - Samin, Noor Ahmad; Datta, Avishek; Soni, Peeyush; Kuwornu, John K.M.; AFG Western Basins Water Resources Management Project; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Impact of integrated nutrient management was investigated on growth and yield of rice in pot experiment under controlled environment condition. A 3{u00D7}3{u00D7}3 factorial experiment with three nutrient levels [100%inorganic, 50%inorganic+50%organic and 100% organic], three different cultivation methods [dry direct seeding (DDS), wet direct seeding (WDS) and transplantation (TP)] and three local rice varieties (Pathumthani-1, RD57, and RD41) was conducted. For inorganic nutrient level, N-P-K (16-16-16) was applied (180 kg/ha) and for organic nutrient level (buffalo manure) was applied (2 t/ha) and it was exposed to a completely randomized design (CRD) with four replications with overall 27 treatments. Moreover, growth parameter, yield and yield components data were collected and then analysis of variance (ANOVA) was carried out with the help of IRRISTAT 5.0 program. In this experiment to detect significant differences among treatment means, least significant differences (LSD) with P< 0.05 was considered. The results revealed that the application of the 100% inorganic nutrient level was high on productive tiller than the other nutrient levels. Moreover, 50% inorganic+50% organic fertilization was also improved shoot dry weight and there was not found any significant difference than 100% inorganic. The 50% inorganic+50%organic nutrient level under DDS method, 100% organic under WDS method and 100% inorganic under TP method had performed well on filled grain per panicle. However, these varieties suffered from the nutrient deficit under TP method of cultivation which was not able to produce more filled grains. Similarly, high number of unfilled grain per panicle was also observed under 100% inorganic nutrient level and 50% inorganic+50% organic and 100% organic nutrient levels decreased by 21.05 under DDS cultivation method. Furthermore, 1000-grain weight was high for Pathumthani-1vareity and there was no significance difference among the method of cultivation, but RD57 variety reduced by 13.88% under WDS than the TP method of cultivation and also no significant difference was found for RD41 under TP and WDS methods. Yield of Pathumthani-1 variety was increased by 22% under TP than WDS and DDS methods of cultivation. There were no statistically differences among 100% inorganic, 50%inorganic+50%organic and 100%organic level for RD41 variety on grain yield. RD57 variety performed well under TP and DDS methods of cultivation on grain yield and there was no significant difference for RD41 variety under TP and WDS methods.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Plant nutrients -- Management; Rice -- Water requirements; Water-supply, Agricultural